Energy optimisation on wastewater treatment plants focusing on different aeration technology - Strassberger, Divan (Department of Civil Engineering, 2020)
With ever more pressure being exerted on South Africa to reduce its carbon emissions and their sole energy producer, Eskom, on the verge of collapse, electricity cost in South Africa are set to increase drastically. It is therefore important that electrical consumption be reduced throughout all sectors and wastewater treatment is no exception. With reduction of electrical consumption of WWTPs in mind, this thesis focused on the costing and viability of replacing less efficient aeration technology (slow speed surface aeration) with more efficient technology (fine bubble diffused aeration). The main objective of the investigation was to calculate the total cost (capital, maintenance and operational) of the two technologies, with the input of the varying inflow rates and wastewater characteristics, and find the inflow rate where the total cost of the two technologies are the same. This intersection was titled the Viability Threshold Point. With this point known it is possible to advise designers and investors as to when and where which aeration technology should be implemented. Different data groups were established with varying wastewater characteristics (see table below) as well as inflow rates varying from 1.0 Mℓ/d to 12.0 Mℓ/d. An inflow COD concentration of 750 mg/ℓ was chosen as a benchmark group and the other inflow characteristics were calculated to represent typical values based on this COD concentration.